Clay Content Played a Key Role Governing Sorption of Ciprofloxacin in Soil - Pasket, Amber; Zhang, Hailin; Wang, Yan; Krzmarzick, Mark; Gustafson, John E.; Deng, Shiping (Frontiers in Soil Science, 2022)
Ciprofloxacin is a broad-spectrum antibiotic of the fluoroquinolone class that is used to treat bacterial infections in both humans and animals. Antibiotics released into the environment can select for antibiotic-resistant microorganisms, which negatively affects human and animal healthcare. Understanding soil factors that govern the mobility of ciprofloxacin can facilitate the development of targeted efforts to mitigate potential negative impacts. The objectives were (1) to determine the sorption capacity of ciprofloxacin in soils under acidic conditions; and (2) to reveal relative importance of key soil factors that influence sorption of ciprofloxacin. Evaluations were conducted using 20 soil samples with diverse properties and different cultivation/vegetation history. Sorption capacity ranged from 8 to 141 g kg−1; distribution coefficient (Kd) ranged from 23 to 200 mL kg−1 soil; and soil organic carbon-water partitioning coefficient (Koc) values ranged from 54 to 2,146 mL g−1 organic carbon. Clay content and cation exchange capacity were the most significant factors that influenced sorption capacity and Kd of ciprofloxacin with r values of 0.92*** and 0.64***, respectively. Soil pH had little effect on ciprofloxacin sorption parameters with r < 0.25. pH-independent charges played a predominant role dictating sorption parameters of ciprofloxacin in soil. Cation exchange via interlayer adsorption was a primary sorption mechanism under acidic conditions. Sorption parameters were significantly correlated with organic carbon content in cultivated soils only, resulting in r values of 0.97*** (with sorption capacity) and 0.72*** (with Kd). Cultivation led to changes in the quality of soil organic matter, resulting in changes in the sorption behavior and altered mechanisms of ciprofloxacin sorption in soil. Soils are effective in restraining the mobility of ciprofloxacin through adsorption and the effectiveness increases with clay content.